2004
DOI: 10.1159/000081762
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based versus Clinical Prediction of the Spirometric Response to Lung Volume Reduction Surgery

Abstract: Background: Lung volume reduction surgery (LVRS) improves symptoms and lung function in selected patients with severe emphysema. Objectives: We investigated whether models based on physiologic and radiologic predictors discriminated patients with a favorable from those with a poor spirometric response to LVRS. Methods: Data of a derivation cohort of 70 patients who had previously undergone LVRS served to develop two types of prediction models, lookup functions and logistic regression equations. Presence or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Supplementary table F shows all the external validation studies of the prognostic models for outcome prediction in COPD patients 2325 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary table F shows all the external validation studies of the prognostic models for outcome prediction in COPD patients 2325 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81…”
Section: Resultsmentioning
confidence: 99%
“…The evidence review also identified several studies in disease states other than cancer, CVD, psychological disorders and disability. Other disease areas addressed by this review included respiratory disease (two studies) (35,36), diabetes (one study) (37), epilepsy (one study) (6), Gaucher disease (one study) (38) and muscle mass deficiency (one study) (39). Of these studies, one was a Level 1, two were Level 2, two were Level 3, and one was Level 4 according to the NICE quality ranking criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Although positive results have been reported after EBV treatment in homogeneous emphysema [10], better results are to be expected in very heterogeneous emphysema and particularly lobar emphysema as exemplified by the present case. In clinical studies, only the RV/TLC ratio that was proposed in the mathematical model by Fessler and Permutt [19] was consistently shown to predict a positive functional outcome after surgical lung volume reduction [26,27,28]. Moreover, for EBV treatment, it has been shown that fissure integrity [29] and absence of collateral ventilation [16] are important for achieving lobar atelectasis.…”
Section: Discussionmentioning
confidence: 99%